How does Interpersonal Communication affect the Harmonious Buddhist Family? - Rina Manggalani; Widiyanto Widiyanto; Ine Yudhawati; Vike Aprilianin Marwintaria; Candra Kusuma (Journal of Communication, Religious, and Social Sciences (JoCRSS), 2023)
This study aims to find out efforts to improve family harmony through interpersonal communication. Interpersonal communication plays an essential role in maintaining balance in a family. This research uses a quantitative approach with a survey method. The population studied was the householders of Dharma Dippa Monastery in Central Lampung, totaling 35 respondents, so the sampling used saturated samples. Based on the study results obtained t count of 3.742 and ttable of 35 Respondents with dk n-2, it becomes 35 respondents with a significant level of 0.05 is 1.334. Then it is known that t count ≥ t table with a value of 3.742 ≥ 334 or sig < 0.05 (0.001 < 0.05). So it can be concluded that the two variables have a regression relationship, and there is an influence between the interpersonal communication variable (X) on family harmony (Y), meaning that H0 is rejected and Ha is accepted. There is a positive and significant effect of interpersonal communication on family harmony. The magnitude of the influence of interpersonal communication on family harmony is 54.6%, and other theories outside this study influence the remaining 45.4%.